A Multifluid Perspective on Multimessenger Modeling - Andersson, Nils (Frontiers in Astronomy and Space Sciences, 2021)
This brief review introduces the notion of a relativistic multifluid system---a multi-component system with identifiable relative flows---and outlines a set of models for scenarios relevant for different astronomical observation channels. The specific problems used to illustrate the key principles include superfluid hydrodynamics (with relevance for radio and x-ray pulsar timing and gravitational-wave searches), heat flow (connecting to the problem of neutron star cooling and associated x-ray observations) and the coupling between matter and electromagnetism (linking to explosive phenomena like gamma-ray bursts and more subtle issues like the long-term evolution of a neutron star's magnetic field). We also comment on the coupling between matter and radiation, for which the multifluid approach would seem less appropriate. The main motivation of the survey is to illustrate less familiar aspects that come into play in multifluid problems, establish the relevant ``language'' and provide a platform for more detailed work on these issues.